The severity and direction prevalence rate of patients with a mandible deviation compared to Cobb’s angle - Kimberly Clarissa Oetomo, - (Fakultas Kedokteran Gigi Universitas Airlangga, 2021)
Background: Patients with mandible deviation often have idiopathic scoliosis, which might affect the result of orthodontic and orthopaedic treatment. Orthodontic treatment not only focuses on aesthetic and functional but also orthopaedic stability. A thorough examination is needed to obtain orthopaedic stability by evaluating the occlusion and posture to establish the best strategy of treatment and interdisciplinary approach. Purpose: This study was conducted to assess the correlation between mandible deviation and idiopathic scoliosis. Methods: This is a descriptive-analytic study with a cross-sectional approach. From 60 samples, 35 patients were chosen based on the inclusion criteria of the total sampling technique. Patients were referred to have skull posteroanterior (PA) and a thoracolumbar PA radiograph taken. Skull PA radiographs were analysed with Grummon’s method using the Orthovision program. Cobb’s angle analysis was used by the radiologist to analyse the thoracolumbar PA radiographs. The data gathered was then further analysed using the Spearman test and the Crosstabs test, using SPSS 23.0. Results: Correlation between mandible deviation and the severity of idiopathic scoliosis is not significant (p=0.866). The direction prevalence of mandible deviation towards Cobb’s angle is 54.3% to the right and 45.7% to the left. All patients with mandible deviation have Cobb’s angle. Conclusion: There is no correlation between mandible deviation and the severity of idiopathic scoliosis. However, many cases showed that the direction of mandible deviation and of idiopathic scoliosis is the same.